# Perpendicular Segments

Discussion in 'Algebra' started by nycmathguy, Jun 28, 2021.

1. ### nycmathguy

Joined:
Jun 27, 2021
Messages:
1,039
208
See attachment.

Let me see.

To find d_1 & d_2, use the distance formula.
I then must use the distance again to find the length of the hypotenuse. Finally, express my lengths in terms of the Pythagorean Theorem.

Yes? nycmathguy, Jun 28, 2021

2. ### MathLover1

Joined:
Jun 27, 2021
Messages:
606
594
d1=sqrt((1-0)^2+(m1-0)^2)
d1=sqrt(1+m1^2)

d2=sqrt((1-0)^2+(m2-0)^2)
d2=sqrt(1+m2^2)

hypotenuse= (d1)^2+(d2)^2

hypotenuse= (sqrt(1+m1^2))^2+(sqrt(1+m2^2))^2

hypotenuse=1+m1^2+1+m2^2
hypotenuse=2+m1^2+m2^2.............eq.1

distance between endpoints of hypotenuse is

hypotenuse=sqrt((1-1)^2+(m2-m1)^2)

hypotenuse=sqrt(0+(m2-m1)^2) ............eq.2

from eq.1 and eq.2 we have

2+m1^2+m2^2=sqrt((m2-m1)^2)...square both sides

(2+m1^2+m2^2)^2=(m2-m1)^2.......take sqrt of both sides

2+m1^2+m2^2=m2-m1

2+m1^2+m2^2-m2+m1 =0.....complete squares

(m1 + 1/2)^2 + (m2 - 1/2)^2 + 3/2 = 0..........solve for m1

(m1 + 1/2)^2 =- (m2 - 1/2)^2 - 3/2

m1 + 1/2 =sqrt(- (m2 - 1/2)^2 - 3/2)

m1 + 1/2 =(1/2) sqrt(-4 (m2 - 1) m2 - 7)

m1 =(1/2) sqrt(-4 (m2 - 1) m2 - 7)-1/2

MathLover1, Jun 28, 2021
nycmathguy likes this.

3. ### nycmathguy

Joined:
Jun 27, 2021
Messages:
1,039
208
Great math work as always. What about my reasoning for this thread? Am I wrong in my discussion?

nycmathguy, Jun 28, 2021
MathLover1 likes this.
4. ### MathLover1

Joined:
Jun 27, 2021
Messages:
606
594

MathLover1, Jun 28, 2021
nycmathguy likes this.
5. Joined:
Jun 27, 2021
Messages:
1,039